(untitled) (Baghdad Science Journal, 2022)
Infertility is a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. Worldwide, infertility affects approximately 15% of all couples trying to conceive. Male infertility is responsible for about 50% of the infertility cases. Chromosomal abnormalities and Y-chromosome microdeletions are the most common genetic causes of male infertility. Klinefelter syndrome (KS) is the most prevalent factor of the chromosomal abnormality in the infertile male. Azoospermia Factor (AZF) microdeletions located on the Y chromosome are one of the recurrent genetic cause of male infertility. This study aims to investigate the prevalence of chromosomal anomalies and AZF microdeletions in 296 infertile Kurdish men in Erbil province, 289 patients diagnosed as azoospermia (97.6%) and 7 patients as severe oligozoospermia (2.4%) and 50 healthy men as control group. Twenty nine patients (9.8%) had various chromosomal abnormalities. The most common chromosomal abnormalities were found in sex chromosomes (93.1%; 29/27), among these abnormalities 20 patients (69%) had Klinefelter syndrome 47,XXY karyotype, 4 patients (13.8%) had 45X0/46, Xder(Y), 2 patients (6.9%) had XXY t(11;22)(q25;q13) and 1 patients (3.4%) had Mosaic Turner syndrome 46XY/45X0. The autosomal chromosomal abnormalities (6.9%; 2/29) detected in 2 patients 45, XY, rob (13;14) (q10;q10). Y chromosome microdeletions were found in 10 of 289 patients with azoospermia (3.5%), three of them (30%) had microdeletions in the AZFc region, 3 of them (30%) had microdeletions in the AZFb region, also other 3 patients had microdeletions in the b and c of AZF (AZF b,c) region, and the final one patient (10%) had microdeletions in the all a, b and c (AZF a,b,c) region. Combined Y chromosome microdeletions and chromosomal abnormalities were detected in 3 patients.